2004
DOI: 10.1017/s1740925x05000013
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular localization and secretion of activity-dependent neuroprotective protein in astrocytes

Abstract: Activity-dependent neuroprotective protein (ADNP, ∼123562.8 Da), is synthesized in astrocytes and expression of ADNP mRNA is regulated by the neuroprotective peptide vasoactive intestinal peptide (VIP). The gene that encodes ADNP is conserved in human, rat and mouse, and contains a homeobox domain profile that includes a nuclear-export signal and a nuclear-localization signal. ADNP is essential for embryonic brain development, and NAP, an eight-amino acid peptide that is derived from ADNP, confers potent neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 40 publications
3
89
0
Order By: Relevance
“…At the protein level, ADNP expression was assessed by Western analysis (Furman et al, 2004) using actin as a control. As expected, results showed reduced expression of ADNP at the protein level in ADNP ϩ/Ϫ mice at all ages tested.…”
Section: Adnp Partial Deficiency Results In Multiple Genementioning
confidence: 99%
See 3 more Smart Citations
“…At the protein level, ADNP expression was assessed by Western analysis (Furman et al, 2004) using actin as a control. As expected, results showed reduced expression of ADNP at the protein level in ADNP ϩ/Ϫ mice at all ages tested.…”
Section: Adnp Partial Deficiency Results In Multiple Genementioning
confidence: 99%
“…Recent findings have shown that ADNP may colocalize with microtubules in the cytoplasm of astrocytes (Furman et al, 2004). The tubulin cytoskeleton is intimately associated with neuronal structure and function (e.g., Gozes and Sweadner, 1981), and the pathology of tau, a microtubule-associated protein that loses proper functionality in the hyperphosphorylated state, has been implicated in multiple neurodegenerative diseases related to axonal dysfunction (Mandelkow et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another potential mechanism for the neuroprotective effects of both the glial-derived NPC transplant and the direct astrocytes may be through secretion of activity-dependent neuroprotective protein (ADNP). Recent literature suggests this protein is secreted by astrocytes, while intranasal delivery of a peptide fragment derived from ADNP, termed NAP, has been demonstrated to increase soluble tau, reduce hyperphosphorylation, and reduce cognitive decline observed in tau transgenic mice (Furman et al, 2004;Shiryaev et al, 2009). This mechanism may be an additional effect that the exogenous transplanted astrocytes have on the endogenous populations and thus promotes neuroprotection.…”
Section: Discussionmentioning
confidence: 99%